2020
DOI: 10.1111/jon.12711
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Findings in Brain Reorganization After Spinal Cord Injury: A Review

Abstract: Spinal cord injury (SCI) leads to a general lack of sensory and motor functions below the level of injury and may promote deafferentation‐induced brain reorganization. Functional magnetic resonance imaging (fMRI) has been established as an essential tool in neuroscience research and can precisely map the spatiotemporal distribution of brain activity. Task‐based fMRI experiments associated with the tongue, upper limbs, or lower limbs have been used as the primary paradigms to study brain reorganization followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
0
4
0
1
Order By: Relevance
“…The resting‐state cortex or subcortex reorganization and plastic changes found in the current study appear to be related to brain dysregulation and alteration in SCI patients, which can be used as a strategy for neurorehabilitation 29 . SCI rehabilitation aims to minimize further damage while restoring as much function as possible by attempting to induce spinal and supraspinal neuroplasticity 30 . Compared with healthy controls, patients with SCI (complete and incomplete) showed low fALFF values in the superior medial frontal gyrus.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The resting‐state cortex or subcortex reorganization and plastic changes found in the current study appear to be related to brain dysregulation and alteration in SCI patients, which can be used as a strategy for neurorehabilitation 29 . SCI rehabilitation aims to minimize further damage while restoring as much function as possible by attempting to induce spinal and supraspinal neuroplasticity 30 . Compared with healthy controls, patients with SCI (complete and incomplete) showed low fALFF values in the superior medial frontal gyrus.…”
Section: Discussionmentioning
confidence: 66%
“…29 SCI rehabilitation aims to minimize further damage while restoring as much function as possible by attempting to induce spinal and supraspinal neuroplasticity. 30 Compared with healthy controls, patients with SCI (complete and incomplete) showed low fALFF values in the superior medial frontal gyrus. In addition, fALFF values of this brain area were positively correlated with the motor and sensory scores in SCI patients.…”
Section: Correlation Analyses Between the Mean Z-score Of Falff And D...mentioning
confidence: 95%
“…Finally, given the long-term spinal cord lesion suffered by this participant, we cannot exclude that some plastic changes have occurred in his motor representations in M1, his somatosensory representations in S1, or the connectivity between the two. There is still no consensus about plasticity following spinal cord injury, with some evidence of preserved network organization, some possible changes in grey matter density 45,46 or activation in the sensorimotor cortices 47,48 . It is also not clear how these results at the population level of SCI patients are predictive of changes at the single patient level.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Importantly, recent studies have shown that sensory connections are spared in approximately half of the lesions considered to be complete [50,51]. The purpose of these brief considerations is to highlight the risk of relevant biases that occur in most studies regarding the consequences of an SCI on the CNS, in line with a recent review [52].…”
Section: Reorganization and Stability Of The Lower Limb Representationmentioning
confidence: 98%